Survival outcomes and adverse events in patients with chronic kidney disease after coronary artery bypass grafting and percutaneous coronary intervention: a meta-analysis of propensity score-matching studies - Ye-gui Yang; Nuo Li; Meng-hua Chen (Renal Failure, 2021)
Background The present meta-analysis of propensity score-matching studies aimed to compare the long-term survival outcomes and adverse events associated with coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI) in patients with chronic kidney disease (CKD). Methods Electronic databases were searched for studies comparing CABG and PCI in patients with CKD. The search period extended to 13 February 2021. The primary outcome was all-cause mortality, and the secondary endpoints included myocardial infarction, revascularization, and stroke. Odds ratios (ORs) and hazard ratios (HRs) with 95% confidence intervals (CIs) were used to express the pooled effect. Study quality was assessed using the Newcastle–Ottawa scale. The analyses were performed using RevMan 5.3. Results Thirteen studies involving 18,005 patients were included in the meta-analysis. Long-term mortality risk was significantly lower in the CABG group than in the PCI group (HR: 0.76, 95% CI: 0.70–0.83, p < .001), and similar results were observed in the subgroup analysis of patients undergoing dialysis and for different estimated glomerular filtration rate ranges. The incidence rates of myocardial infarction (OR: 0.25, 95% CI: 0.12–0.54, p < .001) and revascularization (OR: 0.17, 95% CI: 0.08–0.35, p < .001) were lower in the CABG group than in the PCI group, although there were no significant differences in the incidence of stroke between the two groups (OR: 1.24; 95% CI: 0.89–1.73, p > .05). Subgroup analysis among patients on dialysis yielded similar results. Conclusions Our propensity score matching analysis revealed that, based on long-term follow-up outcomes, CABG remains superior to PCI in patients with CKD.